Mitochondrial Respiratory Disorders: A Perspective on their Metabolite Biomarkers and Implications for Clinical Diagnosis and Therapeutic Intervention - Uittenbogaard, Martine (Biomark J, 2015)
Mitochondrial respiratory disorders are incurable progressive degenerative diseases with multi-organ system manifestations. These orphan diseases are caused by mutations in the nuclear or mitochondrial genome affecting the oxidative phosphorylation (OXPHOS) system responsible for ATP synthesis. Currently, therapeutic treatments are not available to patients, resulting in significant disability and a poor prognosis. Patients exhibit a constellation of complex neurological and multisystem phenotypic symptoms. The hallmark of these diseases is their clinical heterogeneity and high variability among patients. Consequently, establishing an accurate diagnosis remains a challenging, invasive, and time-consuming process due to the limited sensitivity, specificity and reliability of the current serum biomarkers used in clinical settings. Recent mouse model-based research combined with patient studies led to the identification of fibroblast growth factor 21 (FGF-21) as a promising serum biomarker. With its high specificity and sensitivity, FGF-21 is a promising diagnostic tool for muscle-affecting mitochondrial respiratory disorders, which might be a useful first-line diagnostic tool instead of the invasive muscle biopsy currently performed in clinical settings. Discovering additional diagnostic biomarkers is critical for establishing an accurate diagnosis given the high clinical heterogeneity of these mitochondrial respiratory diseases. Ultimately, these novel biomarkers might be instrumental to monitor the progression of these diseases and the efficacy of novel therapeutic interventions.